Posterior Interosseous Neurectomy Alternative for Treating Chronic Wrist Pain - Abdelaziz, Ashraf M.; Aldahshan, Wael; El-Sherief, Faisal Ahmed Hashem; Wahd, Yaser El Sayed Hassan; Soliman, Hany Abdel Gawwad (Journal of Wrist Surgery, 2019)
Background Wrist denervation is one of the several available options for treating chronic wrist pain; partial wrist denervation performed through a single dorsal incision by resecting the distal posterior interosseous nerve provides good outcomes.Questions/Purposes This study evaluated the results of posterior interosseous neurectomy (PIN) in patients with chronic wrist pain secondary to scaphoid nonunion advanced collapse (SNAC) and scapholunate advanced collapse (SLAC).Methods In total, 30 wrists obtained from 28 patients (25 males, 3 females) were assessed. The dominant hands of 25 (right-handed) patients, nondominant hands of 5, and both hands of 2 were considered. The average age at the time of surgery was 35 (range: 19–50) years, and the average follow-up duration was 18 (range: 12–30) months. Fifteen and 13 patients had wrists with SNAC and SLAC, respectively, and all of those underwent PIN performed through the dorsal approach. The pre- and postoperative range of motion, grip strength, and pain relief percentage were recorded for all the 30 wrists.Results The average postoperative Disabilities of the Arm, Shoulder and Hand score was 30 (range: 20–80), and the difference between the pre- and postoperative scores was statistically significant. Ninety percent of the patients were satisfied with the results of PIN and reported improvement in grip strength and pain relief.Conclusions Thus, PIN may be an effective surgical technique for wrist reconstruction.Clinical Relevance To help patients challenge pain and maintain their wrist joint range of motion.
Keywords: neurectomy; wrist arthrodesis; wrist joint